Postural evaluation in horses submitted to perineural anesthetic blocks in the thoracic limbs - Lins, Jackellyne Laís Ferreira; Bernardo, Juliana de Oliveira; Mariz, Tobyas Maia de Albuquerque; Escodro, Pierre Barnabé (Seven Editora, 2023)
Lameness is the condition that most distances horses from training days and sports competitions, with the thoracic limbs being the most affected. Despite the great advances in equine sports medicine, diagnostic analgesia probably remains one of the most valuable tools in identifying lameness, with clear and immediate results. Many cases end up evolving into chronic degenerative diseases, which become unresponsive to traditional therapeutic clinical - surgical procedures, indicating the use of drugs or surgical procedures that promote “irreversible” palliative or prolonged reversible analgesia, through interruption of nerve conduction to the region (neurolysis). The palmar/plantar digital nerve is the most submitted to the technique, as the rates of proprioceptive loss are minimal, but there is information that the more proximal the perineural analgesic block, the greater the motor deficit caused. Given the scarcity of information about these risks, this study aimed to perform the postural assessment of horses submitted to anesthetic blocks with bupivacaine of the palmar, palmar metacarpal, ulnar, median and cutaneous muscle nerves, in isolation and at different times, seeking to identify possible dysfunctions associated with the nerve undergoing blockade. Seven healthy adult horses, without locomotor and trotting problems, were evaluated in triplicate, in relation to the following postural reaction tests for the left forelimb: Limb Dorsiflexion Test (PDF); Member Crossing Test (PCM); Sliding Test (PD) and Obstacle Test after perineural anesthetic block with 0.5% bupivacaine. It was concluded that horses submitted to anesthetic blocks from the palmar metacarpal nerve present proprioceptive deficits that can endanger the life of the horse/rider as a whole, and the use of neurolytic agents should be avoided in active athletic horses. DOI: https://doi.org/10.56238/devopinterscie-030